Forms of Representation in the Aristotelian Tradition. Volume Two: Dreaming - Thörnqvist, Christina Thomsen; Toivanen, Juhana (Brill, 2022)
The trilogy Forms of Representation in the Aristotelian Tradition investigates how Aristotle and his ancient and medieval successors understood the relation between the external world and the human mind. It gives an equal footing to the three most influential linguistic traditions - Greek, Latin, and Arabic - and offers insightful interpretations of historical theories of perception, dreaming, and thinking. This second volume focuses on dreaming and analyses some of the most prominent problems connected to dreams as representations. The contributions in this volume address the core Aristotelian texts and their reception, up to and including contemporary scientific discourse on dreaming.